A Novel System for the Production of the Bioactive N-alkylamide ‘Spilanthol’ Through Somatic Embryogenesis in Acmella ciliata Kunth (Cass.): Production of the Bioactive N-alkylamide ‘Spilanthol’ in Acmella ciliata - Neethu Mohan, S; Hemanthakumar, AS; Preetha, TS (Journal of Tropical Life Science, 2023)
Acmella ciliata Kunth (Cass.), a medicinally important plant in the family Asteraceae, has high commercial value because of its traditional phytomedicinal uses. The plant contains many phytochemicals like alkyl amides, alkaloids, tannins, saponins and flavonoids accountable for most of its pharmacological applications. The study presented here reports the callus culture and somatic embryogenesis of this plant thereby raising a novel system for the subsequent production of the N-alkyl amide ‘spilanthol’, the valuable secondary metabolite presents in it. Murashige and Skoog (MS) medium supplemented with auxins either alone or in combination with cytokinins were used for the induction and maturation of somatic embryos. MS medium supplemented with 2,4-D (0.5, 1.0 and 2.0 mg.L-1) produced black friable callus whereas, 1.0 mg.L-1 NAA in combination with 0.5 mg.L-1 BA induced white, slightly purple coloured friable callus which on further subculture to fresh medium induced somatic embryos that germinated into plantlets upon transfer to MS basal medium. The mode of regeneration via somatic embryogenesis was confirmed by histological analysis through free-hand sectioning and stereomicroscopic observation. The plantlets raised through somatic embryogenesis after a short hardening period, were found to acclimatise in the field at 83.33% efficiency and exhibited genetic uniformity with 96.6% similarity in the ISSR analysis. HPLC analysis of in vitro raised embryogenic callus showed 239.512 µg.g-1 spilanthol content which was comparatively higher than the mother plants (92.19 µg.g-1). The bioproduction of the N-alkylamide ‘spilanthol’ through embryogenic callus can be extended for the scale-up production of this bioactive compound using bioreactor technology for the formulation of phytodrugs.